Curious pleasures : a gentleman's collection of beastliness : being a narrative of mankind's curious and carnal deeds and practices ; the whole forming a valuable, interesting and instructive compendium /: a gentleman's collection of beastliness : being a narrative of mankind's curious and carnal deeds and practices ; the whole forming a valuable, interesting and instructive compendium. (2012) - Unknown
No abstract available